Biological functions and research progress of eIF4E - Chen, Xiaocong; An, Yang; Tan, Mengsi; Xie, Dongrui; Liu, Ling; Xu, Benjin (Frontiers in Oncology, 2023)
The eukaryotic translation initiation factor eIF4E can specifically bind to mRNA 5 'end cap structures, mainly regulating translation initiation and preferentially enhancing the translation of carcinogenesis related mRNAs. The expression of eIF4E is closely related to a variety of malignant tumors. In tumor cells, eIF4E activity is abnormally increased, which stimulates cancer cell growth, metastasis and translation of related proteins. The main factors affecting elF4E activity include nuclear regulation, phosphorylation of 4EBPs, phosphorylation and sumoylation of eIF4E. In this review, we summarize the biological functions of eIF4E and the current status of its research, the main influencing factors of eIF4E activity, and the recent progress of eIF4E targeted drugs, in the hope of providing ideas for the research and treatment of multiple malignancies and providing new insights for the development of targeted drugs.